The right to refuse medical treatment from the Malaysian and Islamic law perspectives - Jahn Kassim, Puteri Nemie; Alias, Fadhlina (Universiti Sultan Zainal Abidin (UNiSZA), 2017)
Over the past century, the health care industry has witnessed a strong deference to the principle of patient autonomy. The growing principle of patient autonomy and right of self-determination has established the right to refuse medical treatment to be amongst the fundamental rights of an individual under Malaysian Medical Law. Consequently, a competent adult patient who has been properly informed has the unassailable legal right to refuse any or all medical treatment and a doctor who proceeds to carry out medical treatment without the consent of a competent adult patient commits battery. It thus, becomes irrelevant if the reasons for refusal are considered irrational or the consequence of such decision may lead to the patient’s death. However, the right to refuse medical treatment presupposes a capacity to do so and when the patient documents this refusal in the form of an advance directive, the circumstances in which the directive was created need to be carefully examined to ensure its legality. For Muslim patients, even though the importance of patient autonomy is duly recognized in Islamic law, the advancement of this concept is not without its limitations as it has to evolve within the perimeters of the religion. The right and ability to make their own choices and decisions about medical care and treatment for Muslims must be within the defined limitations of the Sharī’ah. The emphasis on individualism, personal gratification and the denial of faith in medical decision making is inconsistent with Islamic values. By employing qualitative research method, namely, doctrinal analysis, this research paper seeks to discuss and clarify the legal position under the Malaysian and Islamic law with regards to the right of an individual to refuse medical treatment in the modern health care setting.